PENGARUH LINGKUNGAN KERJA FISIK, KARAKTERISTIK INDIVIDU DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. FLORENCIA AMARA MULIA JAYA KELAPA GADING - Hapidoh Hapidoh; Lidya Pricilla (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the influence of the physical work environment, individual characteristics, and motivation on employee performance at PT Florencia Amara Mulia Jaya Kelapa Gading. This study is quantitative. The method used is quantitative. The sample size was 60 respondents from the employee population, using a saturated sampling technique. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this study indicate that partially the physical work environment (X1) has a positive and significant effect on employee performance (Y) t count > t table or (6.458 > 2.000). Individual characteristics (X2) have a positive and significant effect on employee performance (Y) t count > t table or (5.052 > 2.000). and motivation (X3) has a positive and significant effect on employee performance (Y) t count > t table or (4.648 > 2.000). The value of F count > F table or (30.121 > 2.769) was obtained. With multiple linear regression analysis Y = 23.670 + 0.932 X1 + 0.325 X2 + 0.123 X3 and the contribution coefficient of determination was 51% while the remaining 49% was influenced by other factors.